(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article substantiates the need to clarify the criteria of labor efficiency in connection with the existence of three economic models in the Russian economy: market, state-monopolistic and mobilization. In the economies of market and state-monopolistic types of the criterion of labor efficiency is the maximization of profit received from each unit of resource (labor costs) in value terms. The criterion of labor efficiency in the economy of mobilization type is the maximization of the volume of production of products, works, services received from each unit of labor inputs in natural terms. Fragmentary data on labor productivity in Russia in 2019-2022 are given.